On the nightglow polarisation for space weather exploration ... : في استقطاب الوهج الليلي لاستكشاف طقس الفضاء ... - Léo Bosse; Jean Lilensten; Nicolas Gillet; S. Rochat; A. Delboulbé; Stéphane Curaba; A. Roux; Y. Magnard; Magnar G. Johnsen; U. P. Løvhaug; Pierre‐Olivier Amblard; Nicolas Le Bihan; et al. (OpenAlex, 2020)
We present here observations of the polarisation of four auroral lines in the auroral oval and in the polar cusp using a new ground polarimeter called Petit Cru . Our results confirm the already known polarisation of the red line, and show for the first time that the three other lines observed here (namely 557.7 nm, 391.4 nm and 427.8 nm) are polarised as well up to a few percent. We show that in several circumstances, this polarisation is linked to the local magnetic activity and to the state of the ionosphere through the electron density measured with EISCAT. However, we also show that the contribution of light pollution from nearby cities via scattering can not be ignored and can play an important role in polarisation measurements. This series of observations questions the geophysical origin of the polarisation. It also leaves open its relation to the magnetic field orientation and to the state of both the upper atmosphere and the troposphere. ... : نقدم هنا ملاحظات حول استقطاب أربعة خطوط شفقية في الشفق البيضاوي وفي الشرفة القطبية باستخدام مقياس استقطاب أرضي جديد يسمى Petit Cru . تؤكد نتائجنا الاستقطاب المعروف بالفعل للخط الأحمر، وتظهر لأول مرة أن الخطوط الثلاثة الأخرى التي لوحظت هنا (وهي 557.7 نانومتر و 391.4 نانومتر و 427.8 نانومتر) مستقطبة أيضًا بنسبة تصل إلى بضعة بالمائة. نظهر أنه في عدة ظروف، يرتبط هذا الاستقطاب بالنشاط المغناطيسي المحلي وبحالة الأيونوسفير من خلال كثافة الإلكترون المقاسة باستخدام EISCAT. ومع ذلك، نظهر أيضًا أنه لا يمكن تجاهل مساهمة التلوث الضوئي من المدن القريبة عن طريق التشتت ويمكن أن تلعب دورًا مهمًا في قياسات الاستقطاب. تتساءل هذه السلسلة من الملاحظات عن الأصل الجيوفيزيائي للاستقطاب. كما أنه يترك علاقته مفتوحة باتجاه المجال المغناطيسي وبحالة كل من الغلاف الجوي العلوي والتروبوسفير. ...